2020
DOI: 10.3390/electronics9091377
|View full text |Cite
|
Sign up to set email alerts
|

Energy Harvesting from Bicycle Vibrations by Means of Tuned Piezoelectric Generators

Abstract: Vibrations of two typical bicycles are measured by means of road tests in bicycle lanes. The analysis of experimental results in terms of power spectral density (PSD) of the acceleration components shows that most of the energy associated to bicycle vibrations is concentrated in a low frequency band (<30 Hz). Since piezoelectric cantilever harvesters achieve the best performance in resonance and the resonant frequency is well above 30 Hz, specific tuning strategies are adopted. A novel mathematical model fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The scientific literature provides different PMU schemes for highly efficient energy conversion. The synchronized switch harvesting on inductor (SSHI) technique has shown the most promising results in boosting the performance of the energy generator [ 25 , 26 ]. Figure 10 represents a PMU based on a SSHI rectifier.…”
Section: Harvesting By Means Of Piezo-patchesmentioning
confidence: 99%
“…The scientific literature provides different PMU schemes for highly efficient energy conversion. The synchronized switch harvesting on inductor (SSHI) technique has shown the most promising results in boosting the performance of the energy generator [ 25 , 26 ]. Figure 10 represents a PMU based on a SSHI rectifier.…”
Section: Harvesting By Means Of Piezo-patchesmentioning
confidence: 99%
“…A broadly used and appealing technique in the optimization of mechanical to electrical power conversion from vibrating structures is the synchronized switch harvesting on inductor (SSHI) technique [36]. By assuming harmonic excitation, the maximum average power generated by a SSHI rectifier can be estimated from the average RMS value of the open-circuit voltage 𝑉 𝑅𝑀𝑆 , with the procedure proposed in [15] and here briefly summarized. The maximum power extracted by the electronic converter is expressed as:…”
Section: Prediction Of Output Powermentioning
confidence: 99%
“…Since cantilever piezo-harvesters attain their best performance much beyond this limit, specific tuning strategies have to be adopted. The possibility of using auxiliary oscillators for tuning cantilever piezo-harvesters was investigated in [15]. It was shown that an auxiliary oscillator with a small mass (5 g) has almost the same effect of a larger tip mass (17 g) in terms of output voltage and stress inside the piezo-layer.…”
Section: Introductionmentioning
confidence: 99%
“…The use of piezoelectric elements as a vibration power generation device is effective for obtaining high voltage [24,25]. A piezo harvester with a cantilever structure that used resonance to increase power generation has been proposed [26]. An energy harvester structure with a liquid chip at the tip of the lever has enabled power generation of approximately 1 mW when mounted on a bicycle [22].…”
Section: Introductionmentioning
confidence: 99%